The Empact of the Developed Caffarel Model on Cognitive Knowledge and Learning the Effectiveness of Long Jump for Students - Salman, Rabih Hazem; Aziz, Ahlam Dara; Ashour, Ismail Abd Zaid (Pubmedia Jurnal Pendidikan Olahraga, 2025)
This research aimed to identify the effect of the developed Caffarel model on cognitive knowledge and learning the long jump skill. The researchers used the experimental method with a two-group design (experimental and control). The research population included first-year students in the College of Physical Education and Sports Sciences, Al-Nusour University College, for the academic year (2024-2025). The population included (213) students. They were divided into five sections. After excluding failed students and club and team players, the researchers randomly selected the sample from sections (A) and (B) into two groups: the control group, including (12) students, followed the curriculum provided by the college, while the experimental group, including (12) students, followed the developed Caffarel model. The model was introduced to the same exercises followed in the college. Ten students were selected for the purpose of the pilot study. Thus, the sample constituted (11%) of the research population. In order to avoid factors that affect the results of the experiment and attribute the differences to the experimental factor, the researchers conducted homogeneity on their research sample in the variables of height, weight and age. Moreover, they conducted a pre-test and prepared two units per week for a period of 8 weeks. The number of educational units was 16, with a duration of 90 minutes for each educational unit. After that, the post-test was conducted. The SPSS was utilized to reach the results and conclusions. The results showed that the developed Caffarel model had a positive impact on the cognitive process. The experimental group outperformed the control group in cognitive knowledge experience. Furthermore, the developed Caffarel model had a positive impact on learning the long jump, as demonstrated by significant differences in favor of the post-test for the experimental and control groups. Thus, this research recommended adopting the developed Caffarel model when teaching track and field activities, including the long jump. It also recommended adopting cognitive knowledge as a basis for educational curricula, in accordance with the requirements for learning various skills.